High Concentration Trypsin Assisted Fast In-Gel Digestion for Phosphoproteome Analysis - LIU, Fang-Jie; YE, Ming-Liang; PAN, Yan-Bo; ZOU, Han-Fa (Fēnxī huàxué, 2015)
Polyacrylamide gel electrophoresis (PAGE) is a powerful protein separation technology. Combined with mass spectrometry, it could identify thousands of proteins in proteomics analysis. However, the time-consuming procedure restricts its broad applications in proteomics study. In this work, it was found that high concentration of trypsin did not compromise subsequent phosphopeptide enrichment after in-gel digestion, but could promote the in-gel digestion. Hence, a new, fast and robust digestion method was established. Firstly, 50 mu g of HeLa cell protein was separated into 5 fractions by SDS-PAGE, and then the proteins were digested with high concentration trypsin for 30 min. Finally, the phosphopeptides were enriched by Ti-IMAC Tip. After liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, about 2000 phosphorylation sites were identified in the experimental group, while less than 1500 phosphorylation sites were identified in control group. With the aid of high concentration of trypsin, in-gel digestion could be completed within only 30 min, and more phosphorylation site identifications and lower percentage of missed cleavages were acquired than those in control experiments. The experiment results demonstrated that high concentration of trypsin could not only accelerate the in-gel digestion, but also improve the phosphoproteome coverage. Figure A was the process of polyacrylamide gel electrophoresis. The proteins were separated by their molecular weights. B was the process of in gel digestion assisted by high concentration of trypsin. C were the acquired peptides extracted from the gel slices. D were the purified phosphopeptides through Ti-IMAC enrichment. Key Words * High concentration trypsin * In-gel digestion * Phosphoproteome analysis